User response to mandatory IT use: a coping theory perspective. Issue 4 (4th July 2018) - Bhattacherjee, Anol; Davis, Christopher J.; Connolly, Amy J.; Hikmet, Neset
Abstract: The introduction of a new information technology (IT) into a workplace often engenders a wide range of responses among users. These responses encompass a variety of emotions, such as excitement, indifference, skepticism, and fear, and behaviors, such as user engagement, avoidance, and workarounds, that are often manifested concurrently in the same work environment. We present a taxonomy of these responses in the context of mandated IT use by classifying user responses as engaged, compliant, reluctant, or deviant. Using a coping theoretic lens, we offer seven propositions to describe the causal factors and processes that drive specific IT user responses and how such responses might change over time. A qualitative analysis of 47 interviews of 42 physicians at a large community hospital over an 8-year period provides support for our taxonomy and propositions. The study's key contributions are that it conceptualizes different types of user responses that may emerge in mandatory IT use settings, elaborates the key drivers of and processes underlying these diverse responses, and suggests how those behaviors may change over time with changes in the coping process.